Prediciton of the remaining service life of superheater and reheater tubes in coal-biomass fired power plants - Asgaryan, Mohammad (Cranfield University, 2013)
As a result of concern about the effects of CO2 emssions on the global warming, there is increasing pressure to reduce such emissions from power generation systems. The use of biomass co-firing with coal in conventional pulverised fuel power plants has provided the most immediate route to introduce a class of fuel that is regarded as both sustainable and carbon neutral as it produces less net CO2 emissions. In the future it is anticipated that increased levels of biomass will be required to use in such systems to accomplish the desired CO2 emissions targets. The use of biomass, however, is believed to result in severe fireside corrosion of superheater and reheater tubing and cause unexpected early failures of tubes, which can lead to significant economic penalties. Moreover, future pulverised fuel power systems will need to use much higher steam temeptures and pressures to increase the boiler efficiency. Higher operating temperatures and pressures will also increase the risk of fireside corrosion damage to the boiler tubing and lead to shorter component life. Predicting the remaining service life of superheater and reheater tubes in coal-biomass fired power plants is therefore an important aspect of managing such power plants. The path to this type of failure of heat exchangers involves five processes: combustion, deposition, fireside corrosion, steam-side oxidation, and creep. Various models or partial models each of these processes are available from existing research, but to fully understand the impact of new fuel mixtures (i.e. biomass and coal) and changing operating conditions on such failures, an integrated model of all of these processes is required. This work has produced an integrated set of models and so predicted the remaining service life of superheater/reheater tubes based on the three frameworks which have been developed by analysing those models used in depicting the five processes: one was conceptual and the other two were based on mathematical model. In addition, the outputs of the integrated mathematical models were compared with the laboratory generated data from Cranfield University as well as historical data from Central Electricity Research Laboratories. Furthermore, alternative models for each process were applied in the model and the results were compared with other models results as well as with the experimental data. Based on these comparisons and the availability of models constants the best models were chosen in the integrated model. Finally, a sensitivity analysis was performed to assess the effect of different model input values on the residual life superheater and reheater tubing. Mid-wall metal temperature of tubes was found to be the most important factor affecting the remaining service life of boiler tubing. Tubing wall thickness and outer diameter were another critical input in the model. Significant differences were observed between the residual life of thin-walled and thick-walled tubes.
Keywords: Coal-biomass; model integration; hoop stress; mid-wall metal temperature; sensitivity analysis